THE ROLE OF LEADER IN EMPLOYEE PERFORMANCE ACHIEVEMENT (STUDIES IN REGIONAL EMPLOYMENT AGENCY SURABAYA) - Sukmo Hadi Nugroho; Heru Kreshna Reza (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
In the organization of human interaction are incorporated in them, such as the relationship with subordinate leaders, that they will work together in performing the tasks that have been planned to achieve organizational goals. A leader in the proficient and skilled capable expected should also be willing and have the willingness to work effectively and efficiently. The task of a leader is to plan, mobilize and supervise every activity in the organization. One of the main tasks of a leader is to be able to achieve the performance of employees which in turn can achieve the goals and objectives of the organization are in leader. The method used in this research is a descriptive qualitative approach His research focus is 1) the role of the leader in achieving the performance of employees at the Regional Employment Agency of Surabaya (BKD). 2) the performance of employees in the Regional Employment Agency of Surabaya. The results showed that the role of the leader in achieving the performance of employees in Surabaya Regional Employment Agency can already be quite well where leaders are able to carry out their role so as to achieve better performance of employees in order to realize the objectives of the organization. Keywords: Leader, Employee Performance, Regional Employment Agency Surabaya